Sustainable Mining 2010 Conference 17 - 19 August, 2010, Kalgoorlie, Western Australia (Publication series (Australasian Institute of Mining and Metallurgy), 2010)
As our mining businesses emerge from the trough in the global commodity cycle, we face increased community and media scrutiny in tackling the ongoing challenge of maintaining the triple bottom line. These social, environmental and economic pillars are critical to the mining industry's 'social licence to operate'. Mining activities are expected to be more than financially and technically sound - they must also balance and embrace the evolving needs of the environment and community. The papers in this proceedings cover themes such as: Sustaining the Business; Increasing Energy Efficiency of Mining and Processing Operations; Reduction, Reuse and Remediation; Sustainable Water Use; Sustaining People, Regions and Communities; Communities and Local Adaptation; Regulatory Frameworks and the Business Case; Health and Safety and Human Resources; Looking Backward, Moving Forward - Lessons from the Goldfields; Climate, Energy and Environmental Risk; and The Future of Mining.--Foreword.